2015
DOI: 10.1186/s12936-014-0524-z
|View full text |Cite
|
Sign up to set email alerts
|

Field assessment of dried Plasmodium falciparum samples for malaria rapid diagnostic test quality control and proficiency testing in Ethiopia

Abstract: BackgroundRapid diagnostic tests (RDTs) are now widely used for laboratory confirmation of suspected malaria cases to comply with the World Health Organization recommendation for universal testing before treatment. However, many malaria programmes lack quality control (QC) processes to assess RDT use under field conditions. Prior research showed the feasibility of using the dried tube specimen (DTS) method for preserving Plasmodium falciparum parasites for use as QC samples for RDTs. This study focused on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 18 publications
4
23
0
1
Order By: Relevance
“…Methods for preparing stable positive controls from cultured P. falciparum using DBS and dried tube specimens (DTS) have been demonstrated ( 68 , 69 ). Tamiru et al reported performance of DTS PT challenges at 1000 and 500 parasites/µL in a field trial in Ethiopia; false negative DTS at 500 parasites/μL were reported after 24 weeks’ storage due to errors in interpreting faint test lines ( 70 ). Aggett reported stability of CD4 PT samples as only 7 days at ambient temperature and 14 days when refrigerated ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Methods for preparing stable positive controls from cultured P. falciparum using DBS and dried tube specimens (DTS) have been demonstrated ( 68 , 69 ). Tamiru et al reported performance of DTS PT challenges at 1000 and 500 parasites/µL in a field trial in Ethiopia; false negative DTS at 500 parasites/μL were reported after 24 weeks’ storage due to errors in interpreting faint test lines ( 70 ). Aggett reported stability of CD4 PT samples as only 7 days at ambient temperature and 14 days when refrigerated ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Partisipasi dalam skema UP diperlukan dan bermanfaat bagi semua laboratorium pengujian. Banyak skema UP telah dilakukan di seluruh dunia dalam berbagai bidang pengujian, seperti di bidang analisis lingkungan (Asiah, 2017), analisis air (Kim et al, 2010), sifat fisik (Hegazy et al, 2010), serum manusia (Carter et.al, 2010), klinis (Tamiru et al, 2015), mikrobiologi (Smith, 2015), dan makanan (Dajay et al, 2019)…”
Section: Pendahuluanunclassified
“…While the world waits for the complete development of PCW, dried Plasmodium falciparum -infected samples were developed as possible cheaper alternatives in monitoring the performance of RDT in routine use [ 9 ]. The dried P. falciparum -infected sample tubes contain the RDT target antigens; histidine rich protein 2 (HRP2), lactate dehydrogenase (LDH) and aldolase [ 9 , 10 ]. The challenge facing their applicability is protein degradation and rapid loss of reactivity during prolonged storage at ambient conditions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dried P. falciparum -infected sample tubes contain the RDT target antigens; histidine rich protein 2 (HRP2), lactate dehydrogenase (LDH) and aldolase [ 9 , 10 ]. The challenge facing their applicability is protein degradation and rapid loss of reactivity during prolonged storage at ambient conditions [ 9 , 10 ]. Furthermore, it is challenging to establish well characterized samples for specific RDTs, as well as quantification of target antigens.…”
Section: Introductionmentioning
confidence: 99%